SAGRADA POESIA MALDITA: o desenvolvimento da cosmovisão homoerótica na obra de Waldo Motta - Martinuzzo, Marcel Bussular (2020)
This study investigates Capixaba poet Waldo Motta`s homo-erotic cosmovision, what it consists of and how it unfolds. Based on a detailed and deep reading of Motta's work, enlightened by literary scrutiny and theory, we intend to show the most important el